2016
DOI: 10.1590/1983-21252016v29n218rc
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Saline Conditions and Nitrogen Fertilization on Citrus Production and Gas Exchanges

Abstract: -In two simultaneous experiments, we evaluated the impact of brackish irrigation water and nitrogen (N) fertilization on the production of citrus (scion-rootstock combinations) and its associated gas exchanges. These experiments were conducted at the Campus of Federal University of Campina Grande, Brazil in a protected environment (shade screens on the sides) using drainage lysimeters. Experiment I used a randomized block design (3 replicates), in a 5 × 3 factorial arrangement, corresponding to five water sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 26 publications
2
26
0
2
Order By: Relevance
“…Hussain et al (2012) subjected citrus to salt stress and reported that a reduction in gs leads to a reduction in CO 2 diffusion. The same trend observed in the present study was also found by Sousa et al (2016), in citrus plants grown with waters of different salinity levels (0.6, 1.2, 1.8, 2.4 and 3.0 dS m -1 ). According to these authors, there is a relationship between transpiration and stomatal conductance, so that a reduction in gs leads to a reduction in E. Gonçalves et al (2010) also observed the existence of this relationship and concluded that the water vapor flow to the atmosphere decreases as the stomata close.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Hussain et al (2012) subjected citrus to salt stress and reported that a reduction in gs leads to a reduction in CO 2 diffusion. The same trend observed in the present study was also found by Sousa et al (2016), in citrus plants grown with waters of different salinity levels (0.6, 1.2, 1.8, 2.4 and 3.0 dS m -1 ). According to these authors, there is a relationship between transpiration and stomatal conductance, so that a reduction in gs leads to a reduction in E. Gonçalves et al (2010) also observed the existence of this relationship and concluded that the water vapor flow to the atmosphere decreases as the stomata close.…”
Section: Resultssupporting
confidence: 92%
“…Reduction of gs in the West Indian cherry is one of the first responses to salt stress. This occurs as a defense mechanism to reduce water loss through the leaves to the atmosphere because water absorption by roots becomes more difficult in saline soil (SOUSA et al, 2016). 1 2 Means followed by the same letter do not differ by Tukey test (p<0.05).…”
Section: Resultsmentioning
confidence: 99%
“…When correlating these values, we verified that the transpiration rate of the plants in the second harvest was 59.2% smaller than the transpiration rate of the first harvest (Figure 2A). The lowest values of stomatal conductance in the second crop ( Figure 1B) indicate that the plants closed part of the stomata due to stress, resulting in a lower transpiration rate (Neves et al, 2009;Sousa et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Sousa et al (2016) observed the inhibition of gas exchanges in irrigated citrus with saline water and Cerqueira et al (2015) observed that the gas exchange in Vitts was negatively affected by water stress. However, the quantification of gas exchange in relation to stress by compaction is variable that still not mentioned in the literature for banana culture that supports the present work.…”
Section: (A) (B)mentioning
confidence: 99%